Current perspectives on the contribution of inhaled corticosteroids to an increased risk for diabetes onset and progression in patients with chronic obstructive pulmonary disease - Herth, Felix; Bramlage, Peter; Müller-Wieland, Dirk (Respiration, 2015)
Recent studies have suggested that inhaled corticosteroids (ICS) play a role in the development of hyperglycemia and type-2 diabetes in patients with chronic obstructive pulmonary disease (COPD). Nevertheless, this corticosteroid-associated adverse effect remains controversial. Moreover, the pharmacokinetic properties and patient characteristics that might contribute to an increased risk for diabetes upon ICS exposure have not been thoroughly investigated. In the present review, we critically discuss current evidence regarding the relationship between ICS therapy in COPD patients and an increased risk for the incidence and progression of type-2 diabetes. In addition, we address therapeutic conditions, clinical implications, and future perspectives related to this potentially important ICS-associated adverse effect in COPD patients.
Published online: November 27, 2014
Gesehen am 27.08.2020